2009
DOI: 10.1097/ajp.0b013e3181aaa909
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Reality on Reducing Pain and Anxiety in Burn Injury Patients

Abstract: This is the first known systematic review to report on the effectiveness of VR, in conjunction with pharmacologic analgesia on reducing pain and anxiety in burn injury patients undergoing wound dressing changes and physiotherapy management compared with pharmacologic analgesia alone or other forms of distraction. Used as an adjunct to the current burn pain management regimens, VR could possibly assist health professionals in making the rehabilitation process for burn patients less excruciating, thereby improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 33 publications
10
145
1
Order By: Relevance
“…In line with the present study Morris et al concluded that by diverting the attention from an unpleasant medical setting to a pleasant and absorbing virtual world, virtual reality can markedly diminish patient's subjective pain experience. [28] In the recent studies conducted by Asvanund et al, [29] Khotana et-al, [8] Fakhurdin et-al and Hoge et al, [1,6] the results are corresponding to the current study where a significant reduction in anxiety and positive behaviour was instilled via the videoeyeglass in pediatric dental patients. Moreover in the present study, sedated children with N2O/O2 showed reduction in anxiety as depicted by pulse rate and Venham's anxiety scores.…”
Section: Discussionsupporting
confidence: 58%
“…In line with the present study Morris et al concluded that by diverting the attention from an unpleasant medical setting to a pleasant and absorbing virtual world, virtual reality can markedly diminish patient's subjective pain experience. [28] In the recent studies conducted by Asvanund et al, [29] Khotana et-al, [8] Fakhurdin et-al and Hoge et al, [1,6] the results are corresponding to the current study where a significant reduction in anxiety and positive behaviour was instilled via the videoeyeglass in pediatric dental patients. Moreover in the present study, sedated children with N2O/O2 showed reduction in anxiety as depicted by pulse rate and Venham's anxiety scores.…”
Section: Discussionsupporting
confidence: 58%
“…The system provides the user with an overall illusion of different senses and creates an immersive experience [10]. Indeed, a range of studies have explored clinical uses of VR, including pain management, physical rehabilitation and psychotherapy [11,12,13]. In recent years, low cost consumer-facing immersive VR systems have become widely available (e.g., Google Cardboard, Gear VR, Oculus Rift 1 ).…”
Section: Virtual Reality and Pain Managementmentioning
confidence: 99%
“…Research in the past decades has suggested that VR technology could provide an alternative solution to pain management [10,11,12,13]. For instance, VR can allow a patient to concentrate on the virtual experience, thus distracting him/herself from the perception of nociceptive signals, and pain [15].…”
Section: Virtual Reality and Pain Managementmentioning
confidence: 99%
“…These results are also in keeping with studies carried out in medical literature, where VR glasses have been used as a distraction to overcome pain, fear, and anxiety in a number of treatment procedures, such as treatment of burn care, chemotherapy, traumatic injuries, injection or blood sampling, and physiotherapy. [10][11][12][13][14][15] The effect of VR distraction in decreasing perceived pain and anxiety can be attributed to a number of reasons. The application of VR distraction is based on the assumption that pain perception has a large psychological component and that pain attracts a strong attentive response because of the potential threat of damaged tissue associated with the sensation.…”
Section: Discussionmentioning
confidence: 99%